Modos de vidas e o cotidiano da população em situação de rua de São Carlos - SP - Agnoli, Marina Dei (Universidade Federal de São Carlos, 2021)
This Scientific Technological Initiation project is involved in the relationship between the demands of the homeless population, the recent integration of social policies and the contribution of promoting social practices and technologies, in the themes of social fragmentation and the processes of social vulnerabilities. Therefore, it proposes to contribute to the analysis of data collected by the 1st Census carried out with the homeless population in the city of São Carlos - SP, carried out in 2019, whose focus will be data related to the daily lives and ways of life of people who find themselves in that situation. The answers were tabulated and systematized using the Excel Office® software, so that graphs and tables were built for analysis, organized into four stages. Throughout the study, it was possible to build the profile of the participants, analyze their ways of life and identify inequalities among the participants, such as the high frequency of people on the streets, low adherence to public facilities and the absence of work in their daily lives. For these underprivileged daily lives, social technologies were proposed, based on the expertise of Occupational Therapy, as strategies that respond to the real needs of this group.
Modos de vida y el cotidiano de personas sin hogar de São Carlos - SP
Ways of life and the daily life of homeless population of São Carlos - SP
Keywords: Terapia ocupacional; Tecnologia social; População em situação de rua; Assistência social; CIENCIAS SOCIAIS APLICADAS